Irregular migrants and the law - Kassim, Azizah; Mat Zin, Ragayah Hj. (2011)
This paper examines Malaysia`s policy on irregular migrants and its implementation, and discusses its impact. A survey and interview covering 404 respondents was conducted between July 2010 and June 2011 to ascertain the real situations surrounding irregular migrants in Malaysia, which is one of the major host countries of international migrants from developing nations. The policy on foreign workers was formulated in the mid-1980s to deal with the large number of irregular migrants and their many negative impacts, which had posed a serious challenge to the security, economy, and political stability of Malaysia.

Legalization was done in stages, the first of which was in 1985 following the signing of the Medan agreement with Indonesia in 1984. Other legalization exercises were implemented in subsequent years. Legalization and amnesty exercises are problematic in some ways. Legalization is aimed at irregular migrant workers only, and does not take into consideration nonworking family members who are with them. In contrast, amnesty targets all irregular migrants, and the purpose is to enable them to go home legally without being charged or asked to pay a compound. However, there are those who are ignorant of how to legalize themselves, and many employers are also opposed to legalization and amnesty because these exercises are disruptive to production and could raise their costs as legalized workers are paid higher wages and given benefits. Discussion is still needed to develop legal systems and mechanisms of implementation to control irregular migrants in Malaysia.
Keywords: Emigration and immigration -- Malaysia; Illegal aliens -- Malaysia